Utilizing AI and Satellite Technology to Measure the Effectiveness of Carbon Trading in East Java Protected Forests - Haryono, Haryono; Rahman, Arief; Zainal, Rifki Fahrial; Santoso, Bagus Teguh; Endarto, Budi (West Science Nature and Technology, 2025)
This study investigates the effectiveness of utilizing Artificial Intelligence (AI) and Geographic Information Systems (GIS) for measuring the impact of carbon trading initiatives on East Java's protected forests. The research integrates satellite imagery, AI-driven land-use classification, and carbon stock analysis to evaluate the environmental, economic, and social outcomes of these programs. Key findings indicate a significant reduction in deforestation and an increase in carbon sequestration, driven by targeted reforestation efforts and financial incentives from carbon trading. Socioeconomic benefits, including enhanced community livelihoods and reduced reliance on unsustainable practices, further underscore the program's success. However, challenges such as leakage effects and data inconsistencies highlight areas requiring improvement. The study concludes that advanced technologies, when effectively integrated, offer transformative potential for sustainable forest management and carbon trading efficacy in Indonesia.